2020
DOI: 10.1096/fj.201902117r
|View full text |Cite
|
Sign up to set email alerts
|

Knee loading repairs osteoporotic osteoarthritis by relieving abnormal remodeling of subchondral bone via Wnt/β‐catenin signaling

Abstract: Osteoporotic osteoarthritis (OPOA) is a common bone disease mostly in the elderly, but the relationship between Osteoporotic (OP) and osteoarthritis (OA) is complex. It has been shown that knee loading can mitigate OA symptoms. However, its effects on OPOA remain unclear. In this study, we characterized pathological linkage of OP to OA, and evaluated the effect of knee loading on OPOA. We employed two mouse models (OA and OPOA), and conducted histology, cytology, and molecular analyses. In the OA and OPOA grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
(123 reference statements)
1
23
0
Order By: Relevance
“…In this regard, both osteoporosis and knee OA are attributed to menopause 32 , 33 . However, the possibility of osteoporosis causing the development of knee OA is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, both osteoporosis and knee OA are attributed to menopause 32 , 33 . However, the possibility of osteoporosis causing the development of knee OA is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…After finishing the right knee loading, the same loading procedure was conducted on the left knee. 16 The sham control and OVX groups received sham loading, in which mice were positioned on the loading table without receiving dynamic loading to the knee. In the current study, loads with 1 N and 5 Hz were given for 6 min/day for 14 consecutive days.…”
Section: Mechanical Knee Loadingmentioning
confidence: 99%
“…12 Mechanical forces play a crucial role in vascular injury and repair, which can directly activate the mechanosensing molecules. 13 We have developed joint loading modalities, 14 in which dynamic lateral loads are applied to synovial joints such as the elbow, 15 knee, 16 and ankle. 17,18 It is considered that mechanical loading induces dynamic deformation in the epiphysis that drives the alteration in intramedullary pressure in the medullary cavity and interstitial fluid flow in the lacunocanalicular network.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA), one of the most severe pathologic changes that often occurs in the temporomandibular joints (TMJs) of patients with temporomandibular disorders, is mainly characterized by progressive cartilage degradation and subchondral bone changes (Glyn-Jones et al 2015). Recent studies have shown that bone marrow mesenchymal stem cells (BMSCs) in the subchondral bone of OA joints release a variety of proteins to exacerbate OA progression (Jiao, Niu, Li, et al 2015; Yang et al 2015; Zheng et al 2020). These studies demonstrated that BMSCs of the subchondral bone play an important pathogenic role during OA progression (Zhen et al 2013; Sun et al 2020); however, the exact pathologic mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%